Clay record of climate change since the mid‐Pleistocene in Jiujiang, south China. (5th October 2012) - Hong, Hanlie; Gu, Yangsheng; Yin, Ke; Wang, Chaowen; Li, Zhaohui
<x xml:space="preserve">Abstract</x> To obtain a better understanding of climate change in south China in the Quaternary, a clay mineralogical study was undertaken on the red earth profile at Jiujiang, using X‐ray diffraction (XRD) and particle‐size distribution analysis methods. The XRD results showed that the clay minerals of the Jiujiang red earth were mainly mixed‐layer illite–smectite (I/S), illite, kaolinite and vermiculite, with trace amounts of mixed‐layer kaolinite–smectite (K/S). Changes in clay mineral composition displayed a trend of three‐stage evolution. The higher mixed‐layer I/S clays and kaolinite contents in the lower portion suggest extremely warm and humid climates over the period c. 700 to c. 350 ka ago. A gradual decrease in I/S clays and kaolinite reveals a gradual climate change from warm/humid to cool/dry during the period c. 350 to c. 130 ka ago. The higher illite and vermiculite contents indicate a relatively cool and dry climate during the period since c. 130 ka ago. The particle‐size distribution pattern of the upper section was similar to that of the Xiashu loess, while that of the middle to lower section was similar to those of fluvially reworked red earth. A rapid increase in the abundance of large grain‐size components at 2.6 m depth indicates an intensification of the winter monsoon and a cool and dry climate during the period, in good agreement with results from the clay mineral composition and homogeneous structure. The red earth sequences in south China could probably be used to test the response of tropical to subtropical regions to global climate changes.